Evaluation and characterisation of bioadhesive suppositories formulated using commercial hydrogenated palm kernel stearin - Lau, Hui Ling (2016)
Rectal route of drug administration is particularly useful when patients cannot tolerate orally yet are unable to receive parenteral injections. Furthermore, studies have shown that it may be possible to circumvent first pass metabolism if absorption was localised in lower rectum. This is theoretically achievable if suppositories were bioadhesive.